Analisis Willingness to Pay Pengunjung terhadap Pelestarian Kawasan Wisata Pegunungan Karst Rammang-Rammang Kabupaten Maros - Aliyah Nurulita; Diah Retno Dwi Hastuti; Citra Ayni Kamaruddin; Abd. Rahim; Muhammad Syafri (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Willingness to Pay (WTP) is a method used to ascertain the extent to which individuals are willing to contribute financially to the protection of a specific tourist destination, in this case, the Rammang-Rammang Karst Mountains. It provides insight into the level of financial support tourists are prepared to offer for the preservation of an environment. The objective of this study is to ascertain the factors that influence visitors' willingness to pay for the development of tourist attractions and to determine the value of their WTP. This will enable the establishment of price rates based on their willingness to travel to the Rammang-Rammang Karst Mountains. This research is quantitative in nature, employing data collection techniques such as observation, questionnaires, and interviews with open-ended questions. The findings of the study indicate that the mean value of the WTP among visitors is Rp. The mean value of the WTP is 14,390. This value is greater than the entrance fee rate that has been implemented by the current Rammang-Rammang Karst Mountains tourism manager (POKDARWIS). A number of factors have been identified as influencing the willingness of visitors to pay, including the level of education, income, and the amount of time spent at tourist sites.